O impacto da inteligência artificial no processo de recrutamento e seleção de pessoas - SANTANA, Keila Raquel; SOARES, Luís Henrique dos Santos (251, 2024)
Este trabalho investiga o impacto da Inteligência Artificial (IA) no processo de recrutamento e seleção de pessoas, focando na aplicação da IA para a otimização desses processos. O objetivo é analisar como a implementação da IA pode transformar as práticas de recrutamento, promovendo maior agilidade e assertividade nas contratações. A pesquisa adota uma abordagem qualitativa, baseada na análise de múltiplos estudos de caso que abrangem empresas de diferentes setores de atuação e portes, garantindo uma avaliação mais abrangente das aplicações da tecnologia. Foram selecionadas empresas que utilizam a plataforma Gupy e a inteligência artificial Gaia para otimizar o recrutamento. Os critérios de seleção incluíram a diversidade dos setores e tamanhos das empresas, como o tempo de uso da IA por, pelo menos, um ano. Os resultados indicam que, mesmo com desafios, a IA traz melhorias significativas nos processos de recrutamento e seleção, aumentando a precisão nas contratações e promovendo decisões mais assertivas para as organizações.

This study investigates the impact of Artificial Intelligence (AI) on the recruitment and selection process, focusing on the application of AI to optimize these processes. The aim is to analyze how the implementation of AI can transform recruitment practices, promoting greater agility and assertiveness in hiring. The research adopts a qualitative approach, based on the analysis of multiple case studies that encompass different sectors and company sizes, ensuring a comprehensive evaluation of technology applications. Companies using the Gupy platform and the AI tool Gaia for recruitment optimization were selected. The selection criteria included diversity in sectors and sizes, as well as a minimum usage of AI for at least one year. The results indicate that AI brings significant improvements to recruitment and selection processes, increasing hiring accuracy and promoting more assertive decisions for organizations.

This study investigates the impact of Artificial Intelligence (AI) on the recruitment and selection process, focusing on the application of AI to optimize these processes. The aim is to analyze how the implementation of AI can transform recruitment practices, promoting greater agility and assertiveness in hiring. The research adopts a qualitative approach, based on the analysis of multiple case studies that encompass different sectors and company sizes, ensuring a comprehensive evaluation of technology applications. Companies using the Gupy platform and the AI tool Gaia for recruitment optimization were selected. The selection criteria included diversity in sectors and sizes, as well as a minimum usage of AI for at least one year. The results indicate that AI brings significant improvements to recruitment and selection processes, increasing hiring accuracy and promoting more assertive decisions for organizations.
Keywords: Inteligência artificial; Recursos humanos; Plataforma digital; Gestão e Negócios